2020
DOI: 10.1007/s12282-020-01150-8
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to cyclin-dependent kinase (CDK) 4/6 inhibitors confers cross-resistance to other CDK inhibitors but not to chemotherapeutic agents in breast cancer cells

Abstract: Background Combined endocrine therapy with a cyclin-dependent kinase (CDK) 4/6 inhibitor has been indicated to improve not only progression-free survival, but also overall survival in patients with hormone receptor (HR)-positive, HER2-negative advanced breast cancer. However, resistance to this combination therapy inevitably develops. How to manage this resistant breast cancer is one of the most important clinical issues. To investigate the mechanisms of action responsible for resistance, we developed breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Another limitation of the current analysis is the use of cells that are resistant to a single CDK4/6 inhibitor, palbociclib. Preclinical evidence in some ER+ models suggests that resistance to palbociclib confers cross-resistance to the other CDK4/6 inhibitors and thus, it is likely that a number of mechanisms of resistance described here will be shared with other CDK4/6 inhibitors [45]. Nevertheless, the data presented here will help guide future efforts to study these potentially targetable alterations in response to CDK4/6 inhibition in TNBC.…”
Section: Discussionmentioning
confidence: 74%
“…Another limitation of the current analysis is the use of cells that are resistant to a single CDK4/6 inhibitor, palbociclib. Preclinical evidence in some ER+ models suggests that resistance to palbociclib confers cross-resistance to the other CDK4/6 inhibitors and thus, it is likely that a number of mechanisms of resistance described here will be shared with other CDK4/6 inhibitors [45]. Nevertheless, the data presented here will help guide future efforts to study these potentially targetable alterations in response to CDK4/6 inhibition in TNBC.…”
Section: Discussionmentioning
confidence: 74%
“…Preclinical data are discordant, as some studies show that CDK4/6i doesn’t have cross-resistance in cellular models, while other studies highlight some mechanism of resistance shared between different CDK4/6i [ 64 ].…”
Section: Treatment Strategies After Cdk4/6i: What Is Known What Is On...mentioning
confidence: 99%
“…Whether CDK4/6i treatment should be continued beyond the development of disease progression remains to be defined. Recent preclinical studies reported cross-resistance between the three approved CDK4/6i in palbociclib-resistant breast cancer cell models [60,61]. However, some studies suggest that a substantial number of patients continue to derive clinical benefit with abemaciclib after prior palbociclib or ribociclib treatment [62][63][64].…”
Section: Role Of Cdk4/6i After Disease Progressionmentioning
confidence: 99%